PREDIKSI ALOKASI JUMLAH PRODUKSI MINYAK SAWIT DENGAN METODE REGRESI LINIER BERGANDA PADA PT. PALM LAMPUNG PERSADA - Sidik Rahmatullah; Dita Destia (STMIK Dian Cipta Cendikia Kotabumi, 2018)
ABSTRACTPT. Palm Lampung Persada Way Kanan is a company engaged in oil palm plantations that produce crude palm oil. This company often experiences problems in the allocation of palm oil production.This research was conducted using multiple linear regression method to predict the allocation of the amount of palm oil production based on learning data using Microsft Excel 2010 and RapidMiner applications. In this study there are dependent variables (free) and independent variables (bound), namely: dependent variable (raw material, amount of labor, rainfall and land area) while the independent variable (palm oil).Calculations using multiple linear regression methods in determining the allocation of the amount of palm oil production can be used to assist companies in making a decision with predictive value close to the original data processed as learning data with a result of 170.811 and original data of 170 and an error value of 0.002.